2017
DOI: 10.1038/srep39670
|View full text |Cite
|
Sign up to set email alerts
|

The emergent role of small-bodied herbivores in pre-empting phase shifts on degraded coral reefs

Abstract: Natural and anthropogenic stressors can cause phase shifts from coral-dominated to algal-dominated states. In the Caribbean, over-fishing of large herbivorous fish and disease among the long-spined urchin, Diadema, have facilitated algal growth on degraded reefs. We found that diminutive species of urchin and parrotfish, which escaped die-offs and fishing pressure, can achieve abundances comparable to total herbivore biomass on healthier, protected reefs, and exert sufficient grazing function to pre-empt macro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 51 publications
2
47
1
Order By: Relevance
“…comm.). Echinometra viridis has been recorded as more abundant in Bocas del Toro than E. lucunter (Guzmán and Guevara 1998a, b, Sangil and Guzmán 2016a, Kuempel and Altieri 2017, and our qualitative observations found that E. viridis accounts for the vast majority of Echinometra subfossil spines in the cores. The Lytechinus/Tripneustes group is comprised of three species: L. williamsi, L. variegatus, and T. ventricosus.…”
Section: Reconstructing Urchin Community Dynamics and Ecological Driverssupporting
confidence: 55%
See 3 more Smart Citations
“…comm.). Echinometra viridis has been recorded as more abundant in Bocas del Toro than E. lucunter (Guzmán and Guevara 1998a, b, Sangil and Guzmán 2016a, Kuempel and Altieri 2017, and our qualitative observations found that E. viridis accounts for the vast majority of Echinometra subfossil spines in the cores. The Lytechinus/Tripneustes group is comprised of three species: L. williamsi, L. variegatus, and T. ventricosus.…”
Section: Reconstructing Urchin Community Dynamics and Ecological Driverssupporting
confidence: 55%
“…Echinometra dominates the subfossil assemblage over the past 3000 yr, comprising on average 85% of urchin spine weight, followed by Lytechinus/ Tripneustes (12%), then Diadema (3%). The vast majority of Echinometra spines were E. viridis, which has been described as the dominant urchin at all depths on modern reefs in Bahia Almirante (Guzmán and Guevara 1998a, b, Sangil and Guzmán 2016a, Kuempel and Altieri 2017 and whose spines dominated the spine assemblage in reef cores collected in a previous study in Bahia Almirante (Aronson et al 2004). Analysis of temporal trends in abundance corrected for sediment weight shows an increase in Echinometra, Lytechinus/ Tripneustes, and all urchins and a decline in Diadema across the full time series when all cores are combined (Fig.…”
Section: Long-term Trends In Urchin and Coral Communitiesmentioning
confidence: 72%
See 2 more Smart Citations
“…The long-term effects of hypoxia are potentially different from, and more substantial than, those of other disturbances on coral reefs because hypoxia affects a broad range of taxa including consumers, habitat formers, and pathogens. However, at least some functional groups show high resilience, because several years after the event the diversity and abundance of mobile invertebrates on previously hypoxic reefs was found to be the same as, or higher than, the diversity and abundance on unaffected reefs (33), and grazing pressure has been sufficient to preempt overgrowth of dead coral by algae (34).…”
Section: Significancementioning
confidence: 99%